Capital Structure and Profitability: Moderating Role of Firm’s Size - Balami, Surya; Koirala, Prakriti (Nepalese Journal of Management Science and Research, 2024)
The profitability of a firm measures its gains over its operative years. Most managerial decisions are ultimately related to improving their company’s profitability. This study attempts to make a rigorous empirical examination of the relationship between capital structure and profitability, and the moderating role of size of firm in this relationship. It develops multiple regression model and assesses the dummy indicator regression of the variables used and discusses the results of the analysis, which indicate that capital structure has no or very little impact on return on equity. Debt ratio has significant positive impact on return on assets while debt-equity ratio has significant negative. Likewise, the size of the firm is not moderating the relationship between capital structure and profitability. While acknowledging that there is no established theory describing the relationship between these two major constructs in finance, this study attempts to provide some of the empirical support that there is a positive association between debt ratio and return on assets while negative between debt equity ratio and return on assets. This paper concludes with a number of implications and research directions for both academics and financial managers, including the need to investigate the comprehensive impact of capital structure on profitability with more rigorous data.